Prótese de palato em sujeitos com disfunção velofaríngea: expectativa e ansiedade - Pinto, Roberta Ribeiro; Macedo, Camila de Cássia; Trindade Júnior, Alceu Sérgio; Feniman, Mariza Ribeiro; Dutka-Souza, Jeniffer de Cássia Rillo; Calais, Sandra Leal [UNESP] (My University, 2010)
Cleft lip and palate (CLL) is a very common craniofacial anomaly. The cleft is usually corrected with surgery which may fail resulting in velopharyngeal dysfunction (VPD). The use of palatal prosthesis is an alternative treatment for correcting both, CLP and VPD. This study evaluated anxiety symptoms expectations of subjects of both genders, with velopharyngeal dysfunction, referred to palatal prosthesis program for VPD treatment. In this cross sectional and descriptive study 30 subjects with velopharyngeal dysfunction, aged 15 to 64 years old (mean age of 28) were interviewed at the Hospital for Rehabilitation of Craniofacial Anomalies (HRAC). All subjects referred to the palatal prosthesis program at HRAC in the year of 2005 were considered for participation in the study but only the first 30 candidates were included. A questionnaire addressing expectation elaborated by the researcher and the Beck Scale on anxiety were used. All subjects showed expectation regarding speech modification. Changes in professional and affective aspects of their lives after changes in speech were obtained with palatal prosthesis were the most reported expectations. Subjects’ age and gender influenced anxiety levels significantly which were minimum across subjects. High levels of expectation were more frequent than anxiety in the sample population.

Considerando que fissura labiopalatina é uma anomalia importante em nossa realidade clínica, que os procedimentos cirúrgicos têm como objetivo restaurar a forma e a função normal das estruturas alteradas, e que muitas vezes sujeitos com esse tipo de malformação por motivos variados não podem se beneficiar dessa forma de tratamento, sendo indicados outros procedimentos, como, a utilização de Prótese de Palato (PP), o presente estudo tem como objetivo mensurar a gravidade dos sintomas de ansiedade e verificar a expectativa de sujeitos com disfunção velofaríngea (DVF), indicados à colocação da PP. São analisados 30 sujeitos do Hospital de Reabilitação de Anomalias Craniofaciais da USP com DVF, de ambos os gêneros, na faixa etária de 15 a 64 anos, com idade média de 28 anos. Como instrumentos de natureza psicológica, são utilizados um questionário de expectativa formulado pela primeira pesquisadora e o Inventário de Ansiedade de Beck. Ocorre expectativa com relação à modificação da fala em todos os sujeitos referente à: mudança nos aspectos profissional e afetivo, que é a mais relatada; idade e gênero não são fatores relevantes nos níveis de ansiedade; o nível mínimo de ansiedade é o de maior ocorrência, sendo que a expectativa aparece com menor frequência que a ansiedade.
Keywords: Anxiety; Expectation; Palatal prosthesis; Beck Scale; Velopharyngeal dysfunction; Ansiedade; Expectativa; Prótese de palato; Escala de Beck; Disfunção velofaríngea